Malaria infection negatively affects feather growth rate in the house sparrow Passer domesticus. (4th May 2016) - Coon, Courtney A. C.; Garcia‐Longoria, Luz; Martin, Lynn B.; Magallanes, Sergio; de Lope, Florentino; Marzal, Alfonso
Abstract : Birds often face various stressors during feather renewing, for example, enduring infection with blood parasites. Because nutritional resources are typically limited, especially for wild animals, when an individual allocates energy to one physiological system, there is subsequently less for other processes, thereby requiring a trade‐off. Surprisingly, potential trade‐offs between malaria infection and feather growth rate have not been experimentally considered yet. Here, we conducted three studies to investigate whether a trade‐off occurs among feather growth rate, malaria infection and host health conditions. First, we explored whether naturally infected and uninfected house sparrows differed in feather growth rate in the wild. Second, we asked whether experimental inoculation of malaria parasites and/or forcing the renewal of a tail feather. Lastly, we evaluated whether individual condition was affected by experimentally‐induced feather regrowth and/or malaria experimental infection. Our findings showed that feather growth rate was negatively affected by natural malaria infection status in free‐living birds and by experimental infection in captive birds. Furthermore, birds that did not increase body mass or hematocrit during the experimental study had slower feather growth. Together our results suggest that infection with blood parasites has more negative health effects than the growth of tail feathers and that these two processes (response to blood parasite infection and renewal of feathers) are traded‐off against each other. As such, our results highlight the role of malaria parasites as a potential mechanism driving other trade‐offs in wild passerines.